Do patient-reported outcome measures improve after aseptic revision total hip arthroplasty?. Issue 2 (March 2023) - ,; Siddiqi, Ahmed; Warren, Jared; Anis, Hiba K; Barsoum, Wael K; Bloomfield, Michael R; Briskin, Isaac; Brooks, Peter J; Higuera, Carlos A; Kamath, Atul F; Klika, Alison; Krebs, Olivia; et al.
Background: The purpose of this study was to determine patient-reported outcome measures (PROMs) changes in: (1) pain, function and global health; and (2) predictors of PROMs in patients undergoing aseptic revision total hip arthroplasty (rTHA) using a multilevel model with patients nested within surgeon. Methods: A prospective cohort of 216 patients with baseline and 1-year PROMs who underwent aseptic rTHA between January 2016 and December 2017 were analysed. The most common indication for rTHA was aseptic loosening, instability, and implant failure. The PROMs included in this study were HOOS Pain and HOOS Physical Function Short-form (PS), Veterans RAND-12 Physical Component Score (VR-12 PCS), and VR-12 Mental Component Score (MCS). Multivariable linear regression models were constructed for predicting 1-year PROMs. Results: Mean 1-year PROMs improvement for aseptic revisions were 30.4 points for HOOS Pain and 22.1 points for HOOS PS. Predictors of better pain relief were patients with higher baseline pain scores. Predictors of better 1-year function were patients with higher baseline function and patients with a posterolateral hip surgical approach during revision. Although VR-12 PCS scores had an overall improvement, nearly 50% of patients saw no improvement or had worse physical component scores. Only 30.7% of patients reported improvements in VR-12 MCS. Conclusions: Overall, patients undergoing aseptic rTHA improved in pain and function PROMs at 1 year. Although global health assessment improved overall, nearly half of aseptic rTHA patients reported no change in physical/mental health status. The associations highlighted in this study can help guide the shared decision-making process by setting expectations before aseptic revision THA.